Tailorable Stimulated Brillouin Scattering Laser Based on Silicon Ring Waveguides - Wang, Yulei; Li, Kai; Yu, Yu; Li, Sensen; Li, Yunfei; Wang, Wuyue; Song, Changyu; Wang, Zhiyong; Wang, Gong; Zhang, Yong; Lu, Zhiwei; Li, Yuhai; et al. (Frontiers in Physics, 2021)
Stimulated Brillouin scattering (SBS) lasers based on silicon waveguides with large SBS gain, have been widely used in frequency tunable laser emission, mode-locked pulse laser, low-noise oscillator, optical gyroscope, and other fields. However, current SBS lasers still need long waveguide lengths to realize Brillouin laser output, which increases the waveguide losses and is not conductive to be integrated. In this paper, we propose a silicon ring waveguide, in order to tune the frequency of the phonon field of SBS laser based on the silicon substrate of the ring cavity. The simulation results exhibit that the tailorable forward SBS effect is realized in the silicon-based optical waveguide with a large SBS gain up to 1.90 W-1m-1. Particularly, with the mutual restraint between photoelastic and moving boundary effects, the tunable phonon frequencies emitting from 1 GHz to 15 GHz are realized through the conversion among higher order modes by modifying the widths of the ring cavity. Therefore, this silicon waveguide based on ring cavity will provide a new technical scheme for designing tunable SBS lasers by tuning the ring widths. In addition, this enhanced and broadband acoustic radiation will pave the way for hybrid integration in silicon-based optical waveguide, micro-electromechanical system, and CMOS signal processing technology.